Dams Overtopping Scenarios from Catastrophic Landslides in Mountains’ Headwaters: Case Study in Kobe City, Japan - Christopher Gomez (Forum Geografi, 2024)
As a Mw 8.0 Nankai Trough Earthquake is predicted with an 80% probability of occurrence within the next 30 years, the efficiency of check dams in the mountains above Kobe City is a crucial question when considering co-seismic landslide disaster risk management. In the present contribution, the author aimed to define which subsection of the Sumiyoshigawa watershed may be more prone to generate impacts downstream of Kobe City from catastrophic landslides in the headwaters. For this purpose, the present state of the check dams network was analysed from the 2018 LiDAR (Light Detection and Ranging) data, considering the progressive infilling of the structures. As a result, the capacity of the dams in 2018 dropped by about 1/10 of the original designed capacity, arguably because of the heavy rainfall events in 2014 and 2018. Despite this evolution, landslides > 20,000 m3 starting from only one tributary can fill all the dams and flow downstream. This data makes it possible to prioritise dam curation programs, especially because population ageing and shrinking are reducing the manpower and the funds available to maintain the check dams.